Computers vs. community. - Koch, Tom (Quill)
Discusses the contradictory principles of computer-assisted and community-based journalism. Newspeople versus evangelists or academic journalists; Evangelical journalism and its sense of community; Expanded notion of press responsibility; Journalism as tool of American democracy; Connectedness as political tool-cum-audience builder; Theory of journalism based on stories and story content; On-line reportage.